A geografia da pesca: modo de vida e lazer na bacia do Rio Araguari-MG - Braconaro, Fernando (2011)
In this work, fishes we analyze it practised in the basin of the river Araguari-MG, located in the region of the Triângulo Mineiro. In this analysis one took in consideration the abilities, knowledge, importance and meaning of it fishes for that if they venture with this activity. In this way, the inquiry considered the way of life of the urban population and agricultural to understand the transformations of the values and meanings related to it fishes. The research had as objective main to analyze the metamorphosis of this practical in the time and the space. Therefore, we choose the construction of the hydroelectric plants and the formation of the cities as moments of rupture and social transformation. A complex activity fishes it practised in the river for the agricultural inhabitants constituted and it was not disentailed of daily the agricultural one, therefore this age conciliated with the excessively practical ones carried through in the properties. In this context, this activity represented, of one alone time, an alimentary alternative, source of income and leisure, being that, part of the materials used in it fishes were produced artisan in the farms. The success in this activity alone was possible thanks to the knowledge related to the techniques, the habits of the fish and the recognition of the capture places. However, the construction of the hydroelectric plants transformed the dynamics ambient of the river, causing the reduction and extinguishing of diverse species. It fishes but it as practical social, it did not disappear, it resurges with a universe entirely renewed associated to the playful one. In this process, new sensibilities appear in relation to the fish, and the capture of these animals represents a chance to run away from the daily one of the cities and to entertain with the nature. The transformation of this activity becomes evident when is evidenced existence of practical that they prevent it the sacrifice of the fish, beyond the existence of championships of fishes. As playful and esporting activity it fishes, it also promotes transformations in the agricultural space, making possible the sprouting of determined services in the interior of the country properties, promoting the pluriatividade and also the urbanization in determined localities. As complex activity, it was analyzed elaboration of the legislation that fish normatizam it in the basin of the river Araguari strikes, them for the use of the space, of the dated decurrent confrontations of the practical ones in distinct times.